Learning in the Workplace : A toolkit for facilitating learning, and assessment in health, and social care settings - Mulholland, Joan, 1939-; Turnock, Chris (Abingdon, Oxon : Routledge, 2013)
This toolkit is designed for preparing health and social care practitioners for their role in facilitating learning in their workplace. It enables readers to recognise learning opportunities, communicate their professional knowledge, provide students with appropriate support, judge performance, co-ordinate student contact with others in the workplace and develop awareness of the needs of students from diverse backgrounds. With plenty of activities and questions, the reader can assess their knowledge base and apply the concepts in the toolkit to their work setting. This new edition is.
Learning and teaching -- Supporting learning in the workplace -- Reflection on and in the work place -- Assessment in the workplace -- Working with others in the workplace -- Diversity -- Portfolio completion guidelines.
Authors' names reversed on earlier ed.
Includes bibliographical references.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
Added to collection customer.56279.3
Keywords: Paramedical education; Employees -- Training of -- Methodology; Learning; Allied Health Occupations -- education; Inservice Training -- methods; Learning; MEDICAL -- Allied Health Services -- Medical Assistants